Answer
"f'''(x)=120x^2-{\\frac{3}{8}}x^{-\\frac{3}{2}}+3x^{-4}."
According the linearity property of the derivative for any triple of constants c1, c2, c3 and three functions f, g and h we have
(c1f + c2g + c3h)’ = c1f’ + c2g’ + c3h’.
On the other hand the differentiation rule of power function can be written in the form
"(x^{n})'=nx^{n-1}"
Because,"\\frac{1}{x}=x^{-1}" we can write
"f(x)=2x^5+x^{\\frac{3}{2}}-\\frac{1}{2}x^{-1}"
So,
"f'(x)=(2x^5+x^{\\frac{3}{2}}-\\frac{1}{2}x^{-1})'=10x^4+{\\frac{3}{2}}x^{\\frac{1}{2}}+\\frac{1}{2}x^{-2}"
For the second derivative we get
"f''(x)=(10x^4+{\\frac{3}{2}}x^{\\frac{1}{2}}+\\frac{1}{2}x^{-2})'=40x^3+{\\frac{3}{4}}x^{-\\frac{1}{2}}-x^{-3}"
And for the third derivative we have
"f'''(x)=(40x^3+{\\frac{3}{4}}x^{-\\frac{1}{2}}-x^{-3})'=120x^2-{\\frac{3}{8}}x^{-\\frac{3}{2}}+3x^{-4}."
Comments
Leave a comment